Reviews on Environmental Health (De Gruyter, 1986)
Reviews on Environmental Health is an international quarterly periodical that fills the need for rapid publication of specialized comprehensive review articles on hot topics in the field of environmental health. The journal is an inspiring forum for scientists, environmentalists, physicians, engineers and students active in the area of public health, including quality of life.